Use of vimentin immunocytochemical staining for evaluation of atypical cells in voided urine samples. Issue 2 (26th November 2016) - Strojan Fležar, Margareta; Srebotnik‐Kirbiš, Irena; Gutnik, Helena
Abstract : Background: Cytomorphology of exfoliated atypical reactive/repair renal tubular cells (RRTC) can resemble atypical urothelial cells thus suggesting a differential diagnostic question of urothelial neoplasia in urinary cytology. Vimentin expression has been shown in RRTC and used for differentiation from atypical urothelial cells. Methods: The institutional computer database was searched for urinary cytology cases with vimentin immunocytochemical staining (2008–2012). Original cytopathological diagnoses based on cytomorphology and the results of vimentin immunostaining were compared to follow‐up data, including histopathological diagnosis, subsequent urinary cytopathology reports, and clinical findings. Results: Of the 42 cases with vimentin immunocytochemical staining, 33 were positive and 9 negative. Consequently, significant renal disease was found in 9/33 (27%) of vimentin positive cases and nehrolithiasis in 4/33 (12%) of vimentin positive and 1/9 (11%) of vimentin negative cases. Erythrocyturia of undetermined origin was diagnosed in nine cases (seven vimentin positive and two negative). Urinary cytology follow‐up was negative in three vimentin positive cases. Urothelial carcinoma was found in 3/9 (30%) of vimentin negative cases. Thirteen patients were lost to follow‐up. Conclusions: Vimentin immunocytochemical staining could be used as an ancillary method for evaluation of atypical cells in urinary specimens in selected cases with RRTC exhibiting cytological atypia. Unnecessary diagnostic procedures for evaluation of urothelial carcinoma could be avoided in vimentin positive cases and further diagnostic work‐up for evaluation of a significant renal disease could be suggested in vimentin positive cases. Diagn. Cytopathol. 2017;45:85–90. © 2016 Wiley Periodicals, Inc.